2004
DOI: 10.1088/0031-9155/49/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Delivery time comparison for intensity-modulated radiation therapy with/without flattening filter: a planning study

Abstract: The treatment delivery time of intensity-modulated radiation therapy (IMRT) with a multileaf collimator (MLC) is generally longer than that of conventional radiotherapy. In theory, removing the flattening filter from the treatment head may reduce the beam-on time by enhancing the output dose rate, and then reduce the treatment delivery time. And in practice, there is a possibility of delivering the required fluence distribution by modulating the unflattened non-uniform fluence distribution. However, the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 28 publications
5
76
0
Order By: Relevance
“…Cashmore 9 also reported similar results of dosimetric properties for a 6 MV FFF beam using an Elekta Precise linear accelerator. Vassiliev [5][6][7][8]10,11 In addition, some of them suggested novel methods of beam source modeling that could be used to improve the speed of MC-based dose calculation. 8,10 However, these methods are computationally intensive and it is difficult to apply them in clinical treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Cashmore 9 also reported similar results of dosimetric properties for a 6 MV FFF beam using an Elekta Precise linear accelerator. Vassiliev [5][6][7][8]10,11 In addition, some of them suggested novel methods of beam source modeling that could be used to improve the speed of MC-based dose calculation. 8,10 However, these methods are computationally intensive and it is difficult to apply them in clinical treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent research studies have shown that removing FF from the linac head can increase the dose rate considerably, and it may have applications with IMRT and other multi-leaf collimator (MLC)-based modalities. 4,5 A study on IMRT with the FF free photon beam revealed that its dose distribution properties are comparable with those of the standard beam, and the amount of out-of-fi eld dose was decreased using FF free beams. 5 Monte Carlo (MC) method is a powerful tool for analyzing linac head components and infl uencing factors on beam characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A study on IMRT with the FF free photon beam revealed that its dose distribution properties are comparable with those of the standard beam, and the amount of out-of-fi eld dose was decreased using FF free beams. 5 Monte Carlo (MC) method is a powerful tool for analyzing linac head components and infl uencing factors on beam characteristics. 6,7 Thus, the effect of FF on photon energy spectra, depth doses, and beam profi les could be studied by an MC method.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] With the removal of the flattening filter which generates a uniform beam profile for 3D-conformal radiotherapy, the output of the photon beam is highly increased. 6,7 For example, the Varian TrueBEAM linear accelerator can produce 1400 monitor units (MU) and 2400 MU per minute for the 6 and 10 MV photon beams, respectively. This dose rate from the flattening-filter free linear accelerator is about 2-3 times higher than the conventional accelerator producing flattened photon beams, and can shorten the treatment time.…”
Section: Introductionmentioning
confidence: 99%